Patient, physician and geographic predictors of cardiac stress testing strategy in Ontario, Canada: a population-based study. Issue 3 (10th March 2022) - Roifman, Idan; Han, Lu; Fang, Jiming; Chu, Anna; Austin, Peter; Ko, Dennis T; Douglas, Pamela; Wijeysundera, Harindra
Abstract : Objectives: To identify patient, physician and geographic level factors that are associated with variation in initial stress testing strategy in patients evaluated for chest pain. Design: Retrospective cohort study. Setting: Population-based study of patients undergoing evaluation for chest pain in Ontario, Canada between 1 January 2011 and 31 March 2018. Participants: 103 368 patients who underwent stress testing (graded exercise stress testing (GXT), stress echocardiography (stress echo) or myocardial perfusion imaging (MPI)) following evaluation for chest pain. Primary and secondary outcome measures: To identify the patient, physician and geographic level factors associated with variation in initial test selection, we fit two separate 2-level hierarchical multinomial logistic regression models for which the outcome was initial stress testing strategy (GXT, MPI or stress echo). Results: There was significant variability in the initial type of stress test performed, with approximately 50% receiving a GXT compared with approximately 36% who received MPI and 14% who received a stress echo. Physician-level factors were key drivers of this variation, accounting for up to 59.0% of the variation in initial testing. Physicians who graduated medical school >30 years ago were approximately 45% more likely to order an initial stress echo (OR 1.45, 95% CI 1.17 to 1.80) than a GXT. Cardiovascular disease specialists were approximately sevenfold more likely to order an initial MPI (OR 7.35, 95% CI 5.38 to 10.03) than a GXT. Patients aged >70 years were approximately fivefold more likely to receive an MPI (OR 4.74, 95% CI 4.42 to 5.08) and approximately 26% more likely to receive a stress echo (OR 1.26, 95% CI 1.15 to 1.38) than a GXT. Conclusions: We report significant variability in initial stress testing strategy in Ontario. Much of that variability was driven by physician-level factors that could potentially be addressed through educational campaigns geared at reducing this variability and improving guideline adherence.